Studies on the Bacterial Species Associated with Gastroenteritis in Goats - Sebastian Joseph (Department of Microbiology, College of Veterinary and Animal Sciences, 1979)
The information regarding the incidence, etiology and pathogenicity of enteric pathogens in goats is very meagre in our country. The present study is aimed at the isolation, identification and characterisation of Enterobacterial organisms from cases of enteritis in goats. The study also included, determination of sensitivity pattern of the isolates to various chemotherapeutic agents. A total of 190 specimens, which included rectal swabs (60), intestinal contents, portions of large and small intestines (92) and mesenteric lymph nodes (38) collected from live/dead animals were examined for enteric pathogens. From these specimens examined, 86 isolates of Escherichia coli (45.26 per cent), 39 Enterobacter cloacae (20.33 per cent) and two Salmonella (1.05 per cent) were obtained. Of all the E.coli isolates, only one (EC/11) was found to be haemolytic. In addition to the above specimens, eight samples of heart blood and 34 specimens of lung tissues collected from cases of gastroenteritis were also examined for the presence of bacterial organisms. Seven isolates of Streptococcus pyogenes (from lung tissues only), 15 isolates of Klebsiella Pneumoniae (from lung tissues only), and one isolate of Corynebacterium pyogenes (from lung tissues only) were obtained. The ability of haemolytic E.coli (EC/11) to produce necrotoxin on rabbit skin was tested and the lesions produced were of necrotic changes. The strain was also found to be pathogenic to mice when tested. One isolate of Salmonella (S/1) was also tested for its pathogenicity to mice, and found non – pathogenic. Enterotoxin production in rabbit ileal loop was studied with haemolytic (EC/11) and non – haemolytic (EC/15) E.coli. The test materials included peptone water culture, soft agar culture fluid and acetone precipitated culture fluid. The results of the experiment have shown that, non – haemolytic E.coli produced dilatation reaction, while the haemolytic E.coli did not. The lesions noticed in the ileal segments of positive reaction were typical of enteritis. Antibiotic sensitivity studies were conducted using 11 chemotherapeutic agents (Ampicillin, bacitracin, chloramphenicol, erythromycin, gentamicin, kanamycin, nitrofuran, penicillin, streptomycin, sulphonamide and tetracycline) on E.coli Salmonella and Enterobacter cloacae. The result showed that cent per cent isolates of E.coli were sensitive to gentamicin, 95.35 per cent to nitrofuran, 88.37 per cent to chloramphenicol, 60.47 per cent to kanamycin, 40.70 per cent to streptomycin, 8.14 per cent to tetracycline and 2.33 per cent to erythromycin. All the 39 isolates of Enterobacter closcae tested were sensitive to gentamicin and kanamycin, whereas 30 (76.92 per cent) were sensitive to chloramphenicol and nitrofuran and 15 (38.46 per cent) to streptomycin. The drugs of choice for Salmonella were found to be gentamicin, chloramphenicol, nitrofuran and streptomycin.